Free-radical copolymerization of 3-phthalimido-2-hydroxypropyl methacrylate with styrene - Coskun, MF; Demirelli, K; Güzel, D; Coskun, M (John Wiley & Sons Inc, 2002)
Free-radical copolymerizations of styrene and phthalimido-2-hydroxypropyl methacrylate (PHPMA) were carried out at 60 degreesC in a 1,4-dioxane solution in the presence of 2,2'-azobisisobutyronitrile at low conversions < 15%). The copolymer compositions were established by elemental analysis. The monomer reactivity ratios r(1) (PHPMA) and r(2) (styrene) were determined with the linearized copolymerization equations of the Kelen-Tudos and inverted Fineman-Ross methods and with the nonlinear relationship of the Mayo-Lewis method to be r(1) = 1.41 and r(2) = 0.24, r(1) = 1.52 and r(2) = 0.26, and r(1) = 1.15 and r(2) = 0.16, respectively. The monomer reactivity ratios and glass-transition temperatures of the copolymers as functions of the copolymer composition are discussed. (C) 2002 John Wiley Sons, Inc.
Keywords: monomer reactivity ratios; glass-transition temperature; styrene; phthalimide